IMPLEMENTATION OF VALUE EDUCATION IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Rohmat Mulyana Sapdi (Conciencia, 2022)
This study aims to discuss value education through Islamic religious education at SMK Syahida. This research uses descriptive qualitative method. The research subjects were selected by purposive sampling. Data collection techniques include: observation, interview, and documentation. The research subjects were the principal, Islamic Religious Education Teacher, Student Council Advisor, Student Council Management, and Students. Data analysis techniques use data collection, data reduction, data display, and verifying. The results and discussion of this research show that value education implemented at SMK Syahida creates students who obey worship, are democratic, protect the environment, and are tolerant in MA, SMK, and SMA environments. This is evidenced by data verification with a data assessment rubric, that from the results of observations, interviews, and documentation show that value education at Syahida Vocational School is through Islamic religious education. This study concludes that value education is very appropriate through Islamic religious education.